S126 How does knowledge, perceptions and attitudes towards shisha pipe smoking vary amongst university students?. (15th November 2016) - Matharoo, J; Arshad, A; Sadhra, S; Norton-Wangford, R; Jawad, M
Abstract : Background and introduction: Despite clear evidence for the harms of shisha pipe smoking (SPS) its use is increasing amongst university students worldwide. This review explores the evidence for the reasons behind this trend by considering students' perceptions, attitudes towards and knowledge of SPS. Review question: 'How does knowledge, perceptions and attitudes towards SPS vary amongst university students?' This question will examine the rationale for students' shisha use and address their perceptions regarding its addictive properties. Literature searches: Three electronic databases were accessed: MEDLINE, EMBASE and CINAHL. Examples of search terms included "shisha" (and its alternatives), "university", "perceptions". Inclusion criteria: January 1990–April 2016 English language Human studies 57 articles were initially identified, with 21 articles included in the final review after abstract and full-text screening. Throughout this process, three common themes emerged: Reasons for and attitude towards SPS. Perceptions regarding health hazards of SPS. Perceptions regarding addictive properties and ability to quit SPS. Each theme was explored in detail, in order to answer the review question. Review findings: Socio-cultural and peer influences are major contributors in students initiating SPS. SPS 'addiction' has two components: physiological and social. This is compounded by the general perception that SPS is a safer, i.e., less harmful and addictive, and sociable alternative to cigarette smoking. Students believe quitting SPS is 'easy', yet few are able to do so successfully. Conclusion: Policy change is fundamental in tackling the SPS pandemic amongst university students. Interventions, within institutions directly or via social media campaigns, must de-glamorise shisha and highlight its harmful effects. Prior to this, additional longitudinal studies are necessitated to build on existing cross-sectional data and understand temporal changes in students' beliefs to allow better, targeted health promotion.